IMPLIKASI HUKUM TERJADINYA DIS-FUNGSI HAK INISIATIF DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP KEBENARAN KAIDAH PEMBENTUKAN PERATURAN DAERAH - Fatkhurohman Miftachus Sjuhad (Masalah-Masalah Hukum, 2014)
There is a bi-function of the representatives' Initiative Right in constructing local regulations. The problem turns out less understanding of the legislative members of their functions and jobs and of their disorientation in becoming the people's representatives. They should devote their lives to the people they represent,  instead of  looking for jobs and increasing their social status. Other influencing factors are low level of human resources, inequal interest of the commission in making local regulations, weak capability in searching objects as materials for constructing local regulations and unavailability of legal experts